Investigating the Needs for Designing English for Special Purposes Training Course for Field Staff in Abu Dhabi Police General Headquarter - Khairi, Hassan .M (Arab Journal for Sciences and Research Publishing, 2016)
This study aimed at investigating the needs for designing ESP course for Abu Dhabi Police officers whose task is to deal directly with public. A questionnaire was used for this purpose, and date were collected and analyzed. The results indicated that English has a remarkable role in police work as stated by 74 participants . 67 of the participants indicated that they lack sufficient training in English language that meets their job requirements. All questionnaire subjects except 3 emphasized that speaking is the most important skill they need at work place and then comes writing and listening and finally reading. The results of the data collects revealed that 69 of the subjects have difficulties in speaking and listening and in less degree in reading and writing. 52 of the subjects stated that they find it so difficult to understand or respond to native English speakers. 72 of the subjects indicated that they are not able to use English terminologies that related to police at work place . So as stated above the results clearly shown that Abu Dhabi Police staff need a special English course to be tailored for their actual need, rather than the English general course currently applied. The study came to clear results that Abu Dhabi police staff working in the field and directly deal with the public are in need for more special training in English language . the study also suggested that English language skills needed at workplace are of great importance and should be considered when applying English training programs.
Keywords: ESP; language functions; needs analysis; police staff; language skills; language sub-skills